2013
DOI: 10.1007/s00227-013-2184-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating stock structure and trophic relationships among island-associated dolphins in the oceanic waters of the North Atlantic using fatty acid and stable isotope analyses

Abstract: International audienceShort-beaked common dolphins (Delphinus delphis) and Atlantic spotted dolphins (Stenella frontalis) are the two most abundant cetacean species in the oceanic waters of Madeira and the Azores. They are of similar size, occur in similar habitats and are regularly observed in mixed-species groups to forage together. Genetic analyses suggested that, within each species, dolphins ranging around both archipelagos belong to the same panmictic population. We tested the hypotheses that (1) within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 74 publications
(99 reference statements)
1
17
0
Order By: Relevance
“…Stable isotopes constitute a useful tool for investigating diet, habitat use and distribution patterns of animals and in cetaceans they have been widely used to infer population structure . Stable isotopes of carbon (measured as δ 13 C values) and nitrogen (measured as δ 15 N values) have been used mostly as dietary tracers based on the fact that the isotopic composition of these elements present in the tissues of an animal depends on that of its food sources and therefore offers an integrated measure of the prey assimilated over a comparatively protracted period of time .…”
mentioning
confidence: 99%
“…Stable isotopes constitute a useful tool for investigating diet, habitat use and distribution patterns of animals and in cetaceans they have been widely used to infer population structure . Stable isotopes of carbon (measured as δ 13 C values) and nitrogen (measured as δ 15 N values) have been used mostly as dietary tracers based on the fact that the isotopic composition of these elements present in the tissues of an animal depends on that of its food sources and therefore offers an integrated measure of the prey assimilated over a comparatively protracted period of time .…”
mentioning
confidence: 99%
“…For example, several studies have shown that sea surface temperature and food availability may influence D. gigas energetic requirements for growth or reproduction . As the functional storage lipids, SFAs are synthesized to provide an adequate energy source for growth and survival of marine organisms . Hence, geographic variations in SFAs are probably due to the different energy demands of squid inhabiting distinct oceanographic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical tracers, such as fatty acid (FA) profiles and stable isotope ratios, have proven to be powerful indicators to identify the geographic origin of food products . FAs are an important energy source for the growth and survival of marine organisms, and regional differences in FA profiles have been reported at the intraspecific level . These differences are generally associated with the divergent environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study (QUÉROUIL et al 2013) reveals faint stock differences among oceanic dolphins using fatty acid and stable isotope analyses. Our results show little variation between the Azores and Canary archipelagos and between the Bay of Biscay and the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%